Eficiência de herbicidas para a cultura do feijão-caupi (Vigna unguiculata (L.) Walp.) - Silva, Kaliane de Souza (Universidade Federal Rural do Semi-Árido, 2012)
In order to evaluate the efficiency of weedkillers in the culture of caupi beans (Vignaunguiculata (L.)Walp.), an experiment was conducted in split plots distributed in randomized complete block design with four replications and the plots were evaluated nine weedkillers/mixtures (S-metolachlor,bentazon + imazamox, S-metolachlor + bentazon + imazamox, imazamox + fluazifop-p-butyl, imazethapyr + fluazifop-p-butyl, bentazon + fluazifop-p-butyl, bentazon+ imazamox + fluazifop-p- butyl,lactofen + fluazifop-p-butyl, fluazifop-p-butyl) and a control without weedkiller, while the sub-plots, two treatments were evaluated: with weeding and no hoeing, to determine the selectivity and effectiveness of weedkiller, respectively. At 21, 28 and 45 days after planting (DAP) were evaluated visually in the culture of intoxication and weed control. At 45 DAP, was carried out assessment of dry mass of weeds. At harvest, when plants of caupi had 80% of dry pods were evaluated the number of pods per plant, hundred grain weight and yield of caupi as a function of the strategies for weed management. Plants treated with the mixture of weedkillerslactofen + fluazifop-p-butyl suffered severe intoxication, later recovering with delayed flowering and harvest in eight days. The main species of infesting plants were Cleome affinisDC., Trianthemaportulacastrum L., Amaranthusspinosus L., Commelinabenghalensis L. and Digitariabicornis Lam., all of them were efficiently controlled by the weedkillers S metolachlor + bentazon + imazamox and lactofen + fluazifop-p-butyl,while S-metolachlor, bentazon + fluazifop-p-butyl and the imazamox + fluazifop-p-butyl did not exert efficient control over Cleome affinis, Amaranthusspinosus and Trianthemaportulacastrum, respectively. The interference of species Amaranthusspinosus caused reduction in the productivity of treated plots bentazon + fluazifop-p-butyl, similarly to the control without hoeing. Despite the severe intoxication, weedkillerslactofen + fluazifop-p-butyl provided higher yield when compared to other treatments, because it reduces the intense vegetative growth provided by high rainfall during the experimental period. It was concluded that the weedkillers S-metolachlor, bentazon + imazamox, S-metolachlor + bentazon + imazamox, imazamox + fluazifop-p-butyl, imazethapyr + fluazifop-p-butyl, bentazon + fluazifop-p-butyl, bentazon + imazamox + fluazifop-p-butyl,fluazifop-p-butyl were selective for the culture and that the effectiveness of these depends on infesting species in the area
Efficiency of weedkillers for the cultivation of caupi beans
Keywords: Vignaunguiculata (L.); Chemicalcontrol; weed; Vignaunguiculata (L.); Controle químico; Planta daninha; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA